INDIVIDUAL ABOUT COLLECTIVE RISKS IN SPORT AND POSSIBILITIES THEIR COVER - Željko Vojinović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Ones of unavoidable factors by the occupation sports activities and the sport are the sport insurance. Apart from disturb the health, permanently or temporarily, accidents cause occasionally and financial expenses, in smaller or the larger scope of work, depending on from the period of time of rehabilitation emerge violations. The insuring house in that case pays is contracted the amount (the contracted indemnity) the insured person. Every participant in the sport contest would need that possesses the personally insurance. Reasons for the processing of subject are in that that most briefly explained themselves and get to know make the insurance of participant in sport, how individuals so and groups for which act or for which work.